AD Cancri: A shallow contact solar-type eclipsing binary and evidence for a dwarf third component and a 16 year magnetic cycle - S. B. Qian (2018)
CCD photometric observations of AD Cancri obtained from 2000 March 7 to 2004 December 20 are presented. Variations of the light levels at the primary minimum and both maxima are found. Uniform solutions of four sets of photometric data were derived by using the Wilson-Devinney method. The solutions suggest that AD Cancri is a shallow W-type contact binary (f = 8.3% ±1.3%) with a high mass ratio of 1/q = 0.770 ± 0.002. The long-term variation of the light curve is explained by variable dark-spot models of the more massive component star with a possible 17 yr cycle. Our 13 times of light minimum over 5 years, including others collected from the literature, have been used for the period study. The complex period changes can be sorted into a long-term period increase at rate of dP/dt = +(4.94 ± 0.16) × 10-7 days yr-1, a 16.2 yr periodic component (A3 = 0.0155 days), and a very small amplitude period oscillation (A4 = 0.0051 days, P 4 = 6.6 yr). The existence of third light may indicate that there isatertiary component in the binary system. Solving the four-band light curves of Samec & Bookmyer, it is found that the contribution of the tertiary component to the total light of the triple system increases with wavelength, which suggests that it is very cool and may be a very red main-sequence star. The small-amplitude period oscillation may be caused by the light-time effect of the cool tertiary component (M3 ∼ 0.41 M⊙). The 16.2 yr periodic component in the orbital period and the 17 yr cyclic activity of the dark spot on the more massive component both may reveal that the more massive component displays solar-type magnetic activity with a cycle length of about 16 yr. © 2007. The American Astronomical Society. All rights reserved.